The factors influencing homebuyers' perspectives towards eco-friendly housing - Navaneethan, Paranjothi (2023)
As sustainability and environmental consciousness become more and more valued in society, it is critical to comprehend the factors influencing people's real estate decisions. Using quantitative methods, the research takes a comprehensive approach to investigate the various aspects that positively affects homebuyers' perspectives towards eco-friendly housing. The study explores prospective homeowners' knowledge of eco-friendly features, and its impacts. It examines how perceived costs—both short, and long-term—affect how decisions are made. Moreover, the study investigates how homebuyers' trust and preferences are shaped by green certifications like GBI, ENERGY STAR and LEED and their methods in encouraging the conservation of the environment. It is evident that the quality of the environment is deteriorating due to the heavy pollution and rapid urbanization (Mei et al., 2017). The majority of energy used in modern cities is used by buildings, which accounts for almost 30 to 40 percent of all energy consumption and 70 percent of all electricity consumption. As a result, the adoption of ecofriendly methods like energy-efficient practices in the building industry offers enormous potential for reducing energy usage. This has brought forth a dire need for the construction industry to step towards energy efficient housing. In Malaysia, the Green Building Index (GBI) is a first-generation assessment instrument for energy-efficient structures. This was an initiative to boost, promote and stimulate environmentally friendly building practices and safeguard the environment. However, the application of green features to obtain the GBI certification results in higher construction costs for developers, which in turn increases the cost for buyers of green buildings (Wira et al., 2013) This study offers detailed insight into what alters the homebuyers’ perception on eco-friendly housing despite having such a high price point. This thesis seeks to make a significant contribution to the fields of consumer behavior, sustainability, and real estate by thoroughly examining consumer’s behavioral patterns. Policymakers, real estate developers, and other stakeholders should benefit from the findings as well as higher education students and scholars, which should make it easier to promote and adopt eco-friendly housing practices among all walks of life.